Pentingnya Pendekatan STEM (Science, Technology, Engineering, Mathematics) pada Pembelajaran Bahasa Indonesia di SMP Negeri 13 Surakarta - Wipradharma, Mahadhika (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2023)
The purpose of this article is to find out the importance of the STEM approach in learning Indonesian and explain the implementation of STEM in improving critical thinking skills at SMP Negeri 13 Surakarta. This research is a qualitative descriptive research, which describes the importance of developing a STEM approach. The subjects in this research were teachers and students of class VII A of SMP Negeri 13 Surakarta. Meanwhile, the object of this research is the application of the STEM approach to procedural text material. Based on the results of this research, the role of the STEM approach is to provide contextual learning, requiring students and teachers to work together to solve a problem using real innovation that can be realized in the form of thoughts or media. Students become more active in learning, have an increased sense of wanting to help each other, are more confident, and are able to respect others and themselves. Our first application of STEM was that the teacher presented teaching material using power point media. Second, the teacher asks students what they know about procedural texts from the media. Third, the teacher displays procedural text material including the meaning, purpose, elements, types and linguistic characteristics of procedural texts. Fourth, the teacher gives students the opportunity to come forward to explain the structure of the procedural text. Fifth, the teacher explains the steps for compiling procedural texts. Sixth, students discuss in groups to write procedure texts and present their group results.